Menggunjing Relief Candi Borobudur sebagai “Cikal Bakal” Komik Indonesia - Aditya Nirwana (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2020)
Referring to the study of Indonesian Comics, most of the critics and researchers agreed on Indonesia's first comic is Put On, (Kho Wan Gie), published in the 1930s in Sin Po Daily in the form of humorous strip comic medium. Most consider the reliefs of the Borobudur temple, wayang beber, and wayang kulit as "forerunners" of Indonesian comics. This is an odd compilation that considers Put On as the first Indonesian comic while believing the relief of the Borobudur temple as the forerunner to the form of comics as a medium. Also, historically it has no logical connection, both in terms of continuity (continuity) and change (change). Such claims are also related to the triumph of ahistorical traditional notions of comics. This incident caused the relief of Borobudur temple to be dragged into the comic category, or claimed to be the forerunner of Indonesian comics. This essay explores the socio-historio-cultural context to expose this. From the description of the arguments obtained several conclusions that: 1) Relief of the Borobudur temple cannot be approved as the forerunner of Indonesian comics, which have no continuity and also ‘the genealogy line is quite clear; 2) Modern Indonesian comics do not inherit relief or puppet traditions in terms of stylization, technique, material, axonometric revolution and also the direction of reading; 3) The form, structure, characteristics, and mediums of Indonesian comics in the early days of their emergence, were known by Indonesian comic artists through the learning process for foreign painters/artists, or by introducing European and American comics which were sent in advance and transferred to Indonesia.